Analysis of The Influence of Work-Life Balance and Teaching-Administration Workload on Performance of Private School Teachers in Indonesia - Isnawati Osman; Akhmad Ramli; Dina Agnesia Sihombing; Iwan Henri Kusnadi; 5Zahra Khusnul Lathifah (Journal on Education, 2024)
The objective of this study is to ascertain the impact of work-life balance, workload, and autonomy on productivity in the context of remote work. Researchers utilize quantitative methodologies. This study employs informal and descriptive research methodologies. The researchers utilized both primary and secondary sources of information in this investigation. Researchers predominantly utilize surveys and in-depth interviews as sources. Researchers utilize secondary materials such as primary journals, supplemental journals, books, and online articles that are pertinent to their research topic. The study's sample consisted of permanent instructors at private secondary schools who had been employed for a minimum of one year and who conducted their work remotely from home. The research team utilized the SPSS software to analyze and manipulate the data. The study's findings support the concept that autonomy has a favorable impact on work efficiency. The workload variable has no impact on work performance in the meanwhile. Furthermore, there exists a direct relationship between achieving a healthy equilibrium between work and personal life and one's level of productivity and effectiveness in the workplace. Therefore, researchers may infer that workload does not have a significant effect on job performance, although autonomy and work-life balance do.